Improvement of physical properties of calcium phosphate cement by elastin-like polypeptide supplementation - Jang, Ji Hyun; Shin, Sumi; Kim, Hyun Jung; Jeong, Jinyoung; Jin, Hyo Eon; Desai, Malav S.; Lee, Seung Wuk; Kim, Sun Young (Scientific Reports, 2018)
Calcium phosphate cements (CPCs) are synthetic bioactive cements widely used as hard tissue substitutes. Critical limitations of use include their poor mechanical properties and poor anti-washout behaviour. To address those limitations, we combined CPC with genetically engineered elastin-like polypeptides (ELPs). We investigated the effect of the ELPs on the physical properties and biocompatibility of CPC by testing ELP/CPC composites with various liquid/powder ratios. Our results show that the addition of ELPs improved the mechanical properties of the CPC, including the microhardness, compressive strength, and washout resistance. The biocompatibility of ELP/CPC composites was also comparable to that of the CPC alone. However, supplementing CPC with ELPs functionalized with octaglutamate as a hydroxyapatite binding peptide increased the setting time of the cement. With further design and modification of our biomolecules and composites, our research will lead to products with diverse applications in biology and medicine.
Keywords: Biocompatible Materials; Bone Cements; Calcium Phosphates; Dental Cements; Elastin; Hardness; Humans; Materials Testing; Microscopy, Electron, Scanning; Peptides; Physical Phenomena; X-Ray Diffraction